Abducens Nerve Neuropraxia due to Acute Bacterial Rhinosinusitis: Case Report and Literature Review - Abdulrahman Alghulikah; Sarah Alseneidi; Hedayah Alsaady; Ahmed Alhussien; Surayie Al-Dousary; Saud Alromaih; Abdulrahman AlHumaizi (Case Reports in Otolaryngology)
Background. Acute bacterial rhinosinusitis (ABRS) is a common infection of the paranasal sinuses that can lead to complications such as orbital and intracranial extension. The abducens nerve course is adjacent to the sphenoid sinus. Diplopia is rarely the initial presentation of sphenoid sinus pathology. In this article, we present the case of a middle-aged male who presented with diplopia and abducens nerve palsy secondary to ABRS, and we conducted a literature review in search of similar cases. Case Presentation. A 52-year-old male presented with diplopia secondary to ABRS. Imaging revealed the complete opacification of the bilateral sphenoid and frontal sinuses, with the extension of the inflammatory process to the optic nerve and cavernous sinus. The patient underwent a surgical intervention, which revealed a pyocele collection in the opticocarotid recess inside the sphenoid sinuses. After the surgery, the patient received antibiotics and reported a complete recovery. Conclusions. Acute bacterial rhinosinusitis can present with atypical symptoms and lead to serious complications, such as abducens nerve palsy. Early diagnosis, appropriate management, and timely referral to a multidisciplinary team are crucial to preventing residual nerve damage and ensuring favorable outcomes.